Pemanfaatan Potensi Sekam Padi sebagai Sumber Energi Alternatif Ramah Lingkungan dan Meningkatkan Kualitas UMKM di Desa Beringin Kencana - Muhammad Suprapto; Yusup Indra Wijaya; Idzani Muttaqin; Budi Setiadi; Agus Jalpi; Rajak Jamali; Abdan Mustaqim Wardana; Meyrida Riana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The main problem faced by Beringin Kencana Village is the waste of rice husk waste, which is often burned or disposed of without further utilization. The purpose of this study is to optimize the potential of rice husks as an environmentally friendly alternative energy source and to improve the quality of MSMEs in the village. The methods used in this study include surveys and interviews with farmers and MSME actors, SWOT analysis, case studies on the application of technology, and trials of converting rice husks into energy. The results of the study show that the application of rice husk conversion technology has succeeded in reducing waste, providing efficient energy alternatives, and increasing MSME income by 20%. The application of this technology also has a positive impact on the environment by reducing carbon emissions and the use of fossil fuels. With these results, Beringin Kencana Village can be an example for other villages in utilizing agricultural waste sustainably.